Dakwah Tasawuf Akhlaqi pada Moral Generasi Milenial (Studi Kasus Tren Hijab) - Kurniawan, Dicky; Nurrohim, Ahmad Hujaj; Mahdiyah, Zulfa; Khasanah, Kurnia Nur; Ismail, Suldi (Journal of Communication Studies, 2024)
Hijab is an obligation for every Muslim woman, an act that is still closely related to morals and Sufism. The use of hijab, which is widely worn by all Muslim women, has led to an increase in the trend of hijab style. Many Muslim women innovate with the hijab style. However, there is an increasingly diverse trend of hijab, many are used not as a symbol of religious morality and only used as an identity. Hijab, which should be used to cover the aurat, is actually used to show the curves of the body by using religious symbols that are not in accordance with morals. The purpose of this study is to provide knowledge of hijab styles that are in accordance with Islamic law, with a moral Sufism approach. The method in this study uses literature research sourced from previous scientific publications. The research uses a qualitative approach by evaluating and analyzing journals and articles as literature and references. Furthermore, after the data was collected and concluded, the authors used a descriptive analysis method. The results of this research are in the form of an idea, where morality can be interpreted as an idea of behavior or habits whose actions are in accordance with norms and laws. Both connect from the absorption of local and religious culture so that it is balanced as a unity of religious law. Referring to the relationship between Sufism akhlaqi and hijab comes from Sufism which means purifying oneself either physically or mentally. While akhlaqi is a temperament or character and disposition of a person. In essence, moral Sufism has scientific principles that are correlated with religion and Islamic teachings.